MAXSUS TA’LIM EHTIYOJLARIGA EGA BO‘LGAN O‘QUVChILARGA FIZIKA FANINI O‘QITIShDA ADAPTIV TA’LIM MUHITINI YARATISh - Asamatdinova, U. (SCIENCE and SOCIETY, 2025)
The article explores the methodological foundations of teaching physics in an inclusive educational environment. It analyzes approaches to adapting learning materials, organizing learning spaces, and implementing digital technologies to meet the diverse educational needs of students with disabilities. The paper provides concrete examples of effective pedagogical practices that enhance the accessibility and quality of physics education in inclusive classrooms. Special emphasis is placed on the teacher’s role as a coordinator of inclusive interaction.
Keywords: inclusive education; physics teaching; methodology; special educational needs; accessible environment; digital technologies; adaptation